Efficacy of sorafenib as adjuvant therapy to prevent early recurrence of hepatocellular carcinoma after curative surgery: A pilot study - Wang, Shen-Nien; Chuang, Shih-Cheng; Lee, King-Teh (Hepatology research, 2014)
Aim Until now, no effective adjuvant therapy to prevent early recurrence of hepatocellular carcinoma (HCC) after curative treatment has been reported. The aim of this study is to evaluate the clinical benefit of sorafenib as adjuvant treatment in subjects with HCC after hepatic resection. Methods The pilot study was undertaken involving HCC patients who had undergone curative liver surgery with high recurrence risk factors. Time to recurrence and disease recurrence rate were assessed. Sorafenib 400 mg q.d. was administrated continuously for 4 months after hepatic resection. Results A total of 31 patients were enrolled and eligible for final data analysis. The median follow‐up time was 19 months (range, 9.5–30.2). Time to recurrence in the sorafenib arm was 21.45 ± 1.98 months (mean ± standard deviation), compared to 13.44 ± 2.66 months in the control arm (P = 0.006). The median recurrence‐free survival in the sorafenib arm did not reach the data cut‐off date compared to 8 months in the control arm (P = 0.006). The recurrence rate between the two groups was significantly different (29.4% vs 70.7%, P = 0.032). Cox regression analysis showed that taking study medicine was the only prognostic variable associated with HCC recurrence (hazard ratio = 0.24, 95% confidence interval = 0.08–0.75, P = 0.014). Conclusion This study showed that setting sorafenib as adjuvant therapy for HCC to prevent early recurrence after hepatic resection could be a potential indication. The cumulative recurrence‐free survival rate also demonstrated the preventive effectiveness of sorafenib.